Persepsi Ibu Muda dan Keluarga tentang Pemberian Imunisasi (Pendekatan Maternal Sensitivity Models Berbasis Keluarga) - Diyan Indriyani; Susi Wahyuning Asih (Politeknik Negeri Jember, 2017)
Introduction: The health condition of babies is the responsibility of mothers and the family. One effort to avoid a situation of pain in infants is by immunization. Early mothers with infant care experience is still lacking, need to support the family in order to have proper decision-making ability in the care of babies, one of which is immunization. Therefore, the right perception about immunization in infants is critical owned by the mother and the family. Objective: This study has the objective to explore the perceptions of early mothers and families about immunization approach to maternal sensitivity models. Methods: The research design was participatory research approaches (qualitative) and Participatory Action Reseacrh (PRA). The techniques of data collection was Focus Group Discussion (FGD) with 50 early mothers as the participants in Regional Health Center of Sumbersari and Sukorambi Jember who had babies. The sampling was done by using purposive sampling in March-August 2016. The data werethen analyzed using descriptive and qualitative methods. Results: The result showed the general condition of pain often experienced by babies are acute respiratory infections, diarrhea and febrile, although some cases of pneumonia occur. Health official are already running a baby care related programs such as immunization, immunization coverage has been good and meet the target. Perceptions of early mothers about immunizations include: to schedule and type of immunization tend to succumb to the health and family perception about immunization is likely to depend wife and health official. Conclusion: It is concluded that immunization coverage has been on target, but the perception of early mothers and families about immunization still needs to be improved. Recommendations in this research that suggested that synergism cooperation among health official, early mothers and families in the optimization of the perception about immunization.